NEMATÓIDE DO GENÊRO Heterodera DANIFICA A FIGUEIRA - Lordello, Luiz Gonzaga E.; Monteiro, Ailton Rocha; Lordello, Rubens R. A. (REVISTA DE AGRICULTURA, 2015)
NEMATÓIDE DO GENÊRO Heterodera DANIFICA A FIGUEIRA